Serious games and eating behaviors: A systematic review of the last 5 years (2018–2022) - Limone, Pierpaolo; Messina, Giovanni; Toto, Giusi Antonia (Frontiers in Nutrition, 2022)
Background: Serious game intervention has emerged over the years as a popular strategy for solving the problem of unhealthy eating behaviour. This has prompted several scholars to explore its significant impact on eating behaviours, identifying its positive effect on nutritional knowledge and eating behaviours. However, since this research field is yet nascent, an update in knowledge is required to further inform the real-world practice as an alternative intervention for instating healthy eating behaviour. Method: To achieve the object of this research, four electronic databases- Science Direct, Web of Science (WoS), APAPSYclNFO, and Emerald- were searched using predefined keywords (search string) relating to the review topic. A total of 15,107 results were retrieved from the databases. After title, abstract, and full-text screening, 15 studies were included following inclusion criteria. Key findings: The result of this research demonstrated that various designs of serious games comprise an effective intervention for changing eating behaviour in both children and adults and addressed the risks of childhood obesity and overweight. The findings also show that the design of the games is co-designed by different specialists such as a nutritionist, psychologist and developer, among others, as either single or multiple players. The effectiveness of the games was attributed to behaviour techniques (BT), cognitive theories (CT), and socio-cognitive theories (SCT) of behaviour change technique (BCT), incorporating an element of implicit learning in serious games. Feedback and reward were the most reported influencing strategies and self-reporting the evaluation approach. Conclusion: This research contributed significantly to the body of knowledge in the field of serious games as the most recent review of evidence in the research area. Evidence from 93.33% of the included studies confirmed the effectiveness of serious games in addressing eating behaviour. This study concludes that serious games are an effective intervention for improving healthy eating behaviour and decreasing unhealthy eating behaviour and that various elements of behaviour change techniques are essential components of implicit nutritional learning through the games. In addition, it is concluded that the risk of childhood obesity and overweight can be reduced or prevented by leveraging the strength of these games.